2015
DOI: 10.1007/s00705-015-2484-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for and characterization of nervous necrosis virus infection in Pacific cod (Gadus macrocephalus)

Abstract: A mortality rate higher than 90% was observed in a larva-rearing facility for Pacific cod, Gadus macrocephalus, in China. Larvae showing clinical signs of infection were collected. Initial suspicion of nervous necrosis virus (NNV) infection was confirmed by sequencing, absolute quantification real-time PCR (A-qPCR), and electron microscopy. The nucleotide sequence of RNA2 was 1,375 bases long (GenBank no. KM576685), coding for a single ORF corresponding to the capsid protein from residues 21 to 1034. Phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…However, the results support the premise that the prevalence tendency of BFNNV genotype is independent of the temperature of the sea surface, in contrast to RGNNV. Thus, it is possible that low viral concentrations in asymptomatic infected wild fishes like cod [genus Gadus (L.)], which is host species for BFNNV (Mao et al., ; OIE ) and which has been recently caught in large quantities in the waters near Korea (Jung et al., ), or some other endobiosis including molluscs and benthic organisms living in deep sea at consistently low water temperature condition would be one factor contributing to high prevalence of the psychrophilic group of betanodaviruses in shellfish, as BFNNV genotype caused the disease to spread to cultivated cold‐water fishes from wild (Johansen et al., ). On the other hand, all viruses included to each of the two genotypes were detected regardless of the shellfish species specificity and local relativity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results support the premise that the prevalence tendency of BFNNV genotype is independent of the temperature of the sea surface, in contrast to RGNNV. Thus, it is possible that low viral concentrations in asymptomatic infected wild fishes like cod [genus Gadus (L.)], which is host species for BFNNV (Mao et al., ; OIE ) and which has been recently caught in large quantities in the waters near Korea (Jung et al., ), or some other endobiosis including molluscs and benthic organisms living in deep sea at consistently low water temperature condition would be one factor contributing to high prevalence of the psychrophilic group of betanodaviruses in shellfish, as BFNNV genotype caused the disease to spread to cultivated cold‐water fishes from wild (Johansen et al., ). On the other hand, all viruses included to each of the two genotypes were detected regardless of the shellfish species specificity and local relativity.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results support the premise that the prevalence tendency of BFNNV genotype is independent of the temperature of the sea surface, in contrast to RGNNV. Thus, it is possible that low viral concentrations in asymptomatic infected wild fishes like cod [genus Gadus (L.)], which is host species for BFNNV (Mao et al, 2015;OIE 2016) were confirmed to be RGNNV rather than BFNNV (Table 4) (Byrne et al, 2008;Johansen & Sommer, 2001). Thus, these results might show that the RGNNV replication is preferred by the co-existence with another genotype in E-11 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is also reported that RNA1, encoding RdRp, protein B1 and B2, is the key contributing factor for the response to temperature [33], Ciulli et al also considered that RNA1 rather than RNA 2 plays a more important part in thermotolerance of NNV, although RNA2 was found to determine temperature sensitivity as well [34,43]. There is evidence that the RNA1 evolved rapidly than RNA2, indicating a strong selection to respond to various temperature ranges [15,45,46]. In our study, we only analysed the cp gene but not the complete sequence of RNA1 and RNA2.…”
Section: Discussionmentioning
confidence: 99%
“…macrocephalus have been carried out for several years in the lab, Key laboratory of Mariculture & Stock Enhancement in North China′s Sea, Ministry of Agriculture and Rural Affairs, Dalian (Gu et al, 2020; Jiang et al, 2012; Mao, Chen, et al, 2018). However, high mortality during larvae stages is still a big problem (Mao, Jiang, et al, 2018; Mao, Wen, et al, 2015). In our previous study, kinds of immune‐related genes were examined in the early developmental stages using next‐generation sequencing technology (Mao, Li, et al, 2015).…”
Section: Introductionmentioning
confidence: 99%